Ranking of Dystonia Severity by Pairwise Video Comparison. Issue 6 (24th March 2016) - Ellermeyer, Tobias; Otte, Karen; Heinrich, Felix; Mansow‐Model, Sebastian; Kayser, Bastian; Lipp, Axel; Seidel, Adrian; Krause, Patricia; Lauritsch, Katharina; Gusho, Elona; Paul, Friedemann; Kühn, Andrea A.; et al.
Abstract: Background: Reviewers of dystonia rating scales agree on the need to assess symptoms more comprehensively. During the development of a quantitative dystonia assessment by video‐perceptive computing, we devised a video‐based severity ranking as a procedure to create a validation standard without the use of clinical scales. Methods: Thirty‐four patients with dystonia (17 with dystonic tremor) and 2 controls were assessed with clinical scales and video‐recordings of 24 short movement tasks. Two to 4 raters compared multiple permutations of videos from 22 subjects, including 2 healthy controls, until a complete rank order was achieved. Inter‐rater agreement was expressed as normalized Kendall tau distance. Spearman correlations of video rank order with clinical scales and self‐rating were repeated for tremor/nontremor subgroups. Results: Normalized Kendall tau distances were <0.3 for 15 items. The video rank order for sitting and head movements correlated with clinical scales for the whole group (rho 0.52–0.87) and in the subgroup without tremor. In the tremor subgroup such correlation was perceived in the 2 items involving sitting. Video rank order correlated with quality of life self‐rating only in 1 item (arms held in front, palm down). Conclusions: The agreement of video rankings between raters is remarkable. The lack of correlation in the tremor subgroup in several items may be interpreted as tremor being considered in video comparisons but not in clinical scales. This supports video‐based ranking as a more comprehensive rating of dystonia and as a possible validation instrument applicable in situations in which no reference standard is available